Research on Chloride Resisting Properties of Recycled Concrete. Issue 5 (February 2019) - Xu, Qian; Liu, Hong-Mei
Abstract: Chloride ion erosion is one of the main factors leading to the decline in durability of concrete structures. When a building is in a chloride environment, the permeability of the chloride ion is often used to reflect the ability to resist chloride penetration in concrete. Due to the particularity of its raw materials, recycled aggregate concrete determines that its own structure is weaker than natural aggregate concrete, and its resistance to chloride ion penetration is lower. Based on the analysis and summary of relevant research methods at home and abroad, this paper draws some factors worthy of research on the ability of recycled concrete to improve chloride ion resistance and some strengthening methods. And the conclusion will provide direction and recommendations for our further research.